2011
DOI: 10.1073/pnas.1110840108
|View full text |Cite
|
Sign up to set email alerts
|

Protein dynamical transition at 110 K

Abstract: Proteins are known to undergo a dynamical transition at around 200 K but the underlying mechanism, physical origin, and relationship to water are controversial. Here we report an observation of a protein dynamical transition as low as 110 K. This unexpected protein dynamical transition precisely correlated with the cryogenic phase transition of water from a high-density amorphous to a low-density amorphous state. The results suggest that the cryogenic protein dynamical transition might be directly related to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 53 publications
0
24
0
Order By: Relevance
“…248 This finding is striking, as such transitions have previously been observed only around 180-240 K. 284,285 Interestingly, at 110 K also the polyamorphic transition of solvent water occurs. 248,281 However, when avoiding the formation of HDA-type hydration water by cooling an identical protein crystal at ambient pressure, no increase in protein mobility is visible up to 180-240 K. Thus, it seems that the HDA -LDA transition in pressure-vitrified hydration water is accountable for the protein dynamical transition at cryogenic temperatures, whereas the mobility in LDA-type hydration water is not sufficient to trigger the transition at 110 K. One could speculate that this results from the water molecules being more mobile in the HDA than in the LDA state. Indeed, it has been shown that the dynamics in HDA near 110 K are two orders of magnitude faster than in LDA, 286 reaching the relaxation times of an ultraviscous liquid.…”
Section: Other Salt Solutionsmentioning
confidence: 83%
See 2 more Smart Citations
“…248 This finding is striking, as such transitions have previously been observed only around 180-240 K. 284,285 Interestingly, at 110 K also the polyamorphic transition of solvent water occurs. 248,281 However, when avoiding the formation of HDA-type hydration water by cooling an identical protein crystal at ambient pressure, no increase in protein mobility is visible up to 180-240 K. Thus, it seems that the HDA -LDA transition in pressure-vitrified hydration water is accountable for the protein dynamical transition at cryogenic temperatures, whereas the mobility in LDA-type hydration water is not sufficient to trigger the transition at 110 K. One could speculate that this results from the water molecules being more mobile in the HDA than in the LDA state. Indeed, it has been shown that the dynamics in HDA near 110 K are two orders of magnitude faster than in LDA, 286 reaching the relaxation times of an ultraviscous liquid.…”
Section: Other Salt Solutionsmentioning
confidence: 83%
“…In particular this change in glycerol conformation is observed concomitantly with the polyamorphic transition, suggesting that water polyamorphism may also affect the structure and dynamics of solutes (e.g., alcohols, polymers, proteins [247][248][249][250][251][252] ).…”
Section: Other Salt Solutionsmentioning
confidence: 98%
See 1 more Smart Citation
“…Now, considering that the structure of water around a macromolecule plays the important roles in the structural stability and the functional expression of the macromolecule, [74][75][76] it is worthwhile to rethink the behaviors of aqueous solutions from a viewpoint of water polyamorphism. 32,66,68,[77][78][79][80][81][82] Recently, it has been proposed that the polyamorphic transition of solvent water may affect the protein dynamics, for example, the effect of the fragile-to-strong crossover of water on the softening of protein around 220 K [83][84][85] and the relationship between the high-to low-density transition of amorphous ice confined in the protein crystal and the protein dynamical transition around 110 K. 86 However, these experiments were performed using the confined water and the direct interrelationship between the polyamorphic behavior of "bulk" solvent water and the dynamics of solute is unclear. In this study, we showed for the first time that the polyamorphic transition of bulk solvent water affects the molecular vibrations of glycerol directly.…”
Section: Resultsmentioning
confidence: 99%
“…[16,17] In relation to proteins, HDA ice and LDA ice have ag reat impact on bioengineering. [18,19] Crystal ice in biomolecules is as ignificant barrier in the field of cryopreservation.U sing X-ray diffraction, HDA to LDA phase transition under high-pressurec ryocooling has been observed and was accompanied by protein structural relaxation. MD simulations of lysozyme and hydration water was carried out to demonstrate ap rotein glass transition.…”
Section: Mim][nomentioning
confidence: 99%